Food Security for Stunting Prevention with Hydroponic Plant Cultivation in the Tumbang Miri Village - Layang, Samuel; Lailiyah, Binti Nur; Ishudi, Patrisio Chrisbudhi; Oktavia, Ruth Bela; Wulandari, Lala Aprilia; Cahyanti, Meiliana; Wijaya, Sandra; Kadmaer, Kelvin Bryan Pedro; Hasibuan, Tangkas; Agustinus, Nicolas; Safitri, Nafa Riani; Panjung, Edsra; Br Girsang, Hesa Ogina; Prasetyo, Aditya; Yupita; Febiolasari, Santi Dwi (Talenta Publisher, 2023)
Tumbang Miri Village, Gunung Mas Regency has nutritional problems in the community that can cause stunting. Stunting is a growth disorder in toddlers such as body size that is not by their age. One of the solutions offered as an effort to prevent stunting is education about hydroponics to improve family nutrition while increasing family food security. The applied hydroponics is hydroponics with a Wick system. The purpose of this activity is to provide food education to the public as part of stunting prevention efforts and to add insight to the community regarding hydroponics. The method used in this counseling is the lecture method, discussion, question and answer, and the practice of hydroponic planting directly to the community. The impact of this counseling not only adds to the public's insight but also directly teaches the community about the use of plastic waste that can be used as a planting medium